TEACHER CREATIVITY IN QUR’ANIC LITERACY INSTRUCTION (BACA TULIS AL-QUR’AN/BTA) IN IMPROVING THE QUALITY OF QUR’ANIC READING - Ayu Handra Cahyaningrum; Edy Muslimin; Indah Nurhidayati (STKIP Pesisir Selatan, 2026)
This study aims to describe the creativity of Qur’anic Literacy (Baca Tulis Al-Qur’an/BTA) teachers and to analyze its implications for improving the Qur’anic reading quality of tenth-grade students at SMA Islam 1 Surakarta. The study employs a qualitative approach with a case study design, in which participants were selected through purposive sampling, involving BTA teachers, students, and school administrators. Data were collected through observations, semi-structured interviews, and documentation, and were analyzed using an interactive thematic analysis technique. The findings indicate that teacher creativity is reflected in the use of adaptive teaching methods, differentiated strategies based on students’ abilities, and the creation of a supportive and reflective learning environment. These strategies contribute to improvements in reading fluency, accuracy of makhraj, application of tajwid rules, and students’ confidence. The novelty of this study lies in its conceptual synthesis that the improvement of Qur’anic reading quality occurs through the integration of varied methods, differentiated instruction, and teachers’ emotional support as a unified pedagogical system. Furthermore, this study emphasizes that teacher creativity is a contextual and reflective practice in Islamic education, particularly at the senior high school level.